Johann Christoph und Luise Adelgunde Victorie Gottsched Briefwechsel 1722-1766: Oktober 1746 - Dezember 1747 - Gottsched, Johann Christoph (Johann Christoph und Luise Adelgunde Victorie Gottsched Briefwechsel 1722-1766, 2018)
The twelfth volume of Johann Christoph Gottsched's correspondence records his efforts to collect material for a planned history of literature. It ranges from the controversy surrounding the Berlin academy's 1747 essay contest against Leibniz's monadology to the different responses to the rumors that a ghost haunted the Collegium Carolinum in Braunschweig.